Effectiveness of TB-Reminder Application in Improving Medication Adherence and Quality of Life of Lung Tuberculosis Patients in Indonesia - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Chairani, Farahdina; Adini, Syilvi; Subchan, Mohamad; Ferdiyansyah, Ferdiyansyah; Putri, Nabila Septiani; Pratiwi, Rossi; Udin, Baha (Sciences of Pharmacy, 2025)
Poor adherence to anti-tuberculosis (TB) treatment continues to hinder therapeutic success and patient quality of life. This study aimed to evaluate the effectiveness of the TB-R mobile application in improving medication adherence and quality of life among pulmonary TB patients at Pandeglang Regional Hospital. Eighty-six patients were randomized into intervention (n = 43) and control (n = 43) groups. Adherence and quality of life were measured using the Medication Adherence Rating Scale (MARS) and EQ-5D-5L, respectively. After one month, the intervention group demonstrated significantly higher adherence (97.7% vs. 79.0%, p < 0.001) and improvement in mean MARS scores (24.7 vs. 22.7, p < 0.001). Although quality of life gains were not statistically significant overall, notable improvements were observed in anxiety/depression and self-care domains. Demographic factors influenced outcomes: patients aged 29–39 and those living with others showed better adherence, while patients aged 40–50 experienced greater quality of life gains. Women aged 51–60 living alone had decreased adherence despite quality of life improvements. These results suggest that mHealth tools like TB-R can enhance adherence, especially when supported by favorable social and demographic conditions. Tailored digital interventions may optimize treatment outcomes in TB care. Future mHealth app development should consider these social and demographic factors to maximize effectiveness and user engagement.